The Indian Express : reinvention through digital business - Sharma, Sunil; Srinivasan, Anand; Singh, Bhumika (London : Indian Institute of Management, Ahmedabad, 2022)
At the turn of mid-2000, the news industry saw a tectonic shift in the reading habits of people, driven by developments in digital technology. News industry's traditional business model of relying on advertisement income was majorly disrupted. This led to a steep decline in revenues from the print business. The case describes the strategy and organization-building initiatives of a leading newspaper in India, as it transitioned from a print newspaper media ecosystem to a digital news ecosystem. Anant Goenka, a third-generation member of the family, led the digital foray. While Anant created a USD 20 million digital business in 4 years, the path toward the next goal of achieving a topline of USD 150 million in the next 7-8 years was not clear. Furthermore, it might entail transforming the Indian Express Group, with close to 90 years of legacy of strong editorial ideologies, to adapt and embrace the rules of the game of the digital ecosystem. This case presents an excellent opportunity to learn the nature and extent of the challenges involved in building and scaling up a digital news business, including the transition from a traditional newspaper business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Electronic commerce -- Case studies